Internet of Things (IoT) based Energy Tracking and Bill Estimation System - D M Srinivasa; Darshan M; Farman Ahmed; H S Meghana; Kusuma B R (International Journal of Engineering and Management Research, 2022)
Electrical energy is an important form of energy in the present times. For better or worse electricity is indispensable to life as we know it. Although we may not yet be able to produce enough clean energy to power the world, we can reduce environmental damage by learning how to save electricity is becoming a priority for more and more people. The purpose of this project is to design a system which can track and estimate the bill using IOT from anywhere in world. The project design comprises of NodeMCU, four channel relay, OLED display and MIT app Inventor 2 as cloud Interface. Here NodeMCU fetches average consumption detail of loads from and logs estimated bill to the cloud-hosted database, monitors the duration for which each relay in a 4-channel relay module was switched-on, performs calculations, and transmits real-time results to an IoT cloud interface. 4-channel relay module executes switching instructions on loads sent over the internet via the control unit. This paper provides highlights on cloud-hosted database details, hardware design, IoT cloud interface application design, and working principle with mathematical modeling of the proposed system and tested results of this system are discussed, with the cloud-hosted database and IoT cloud interface.